Bigger, faster, stronger: how racist and sexist ideologies persist in college sports - Hextrum, Kirsten (Gender and education, 2020)
US college sports are prime cultural sites of racist and sexist ideological production [Coakley, Jay. 2015. Sport in Society: Issues and Controversies. 11th ed. New York, NY: McGraw-Hill; Eitzen, Stanley D. 2016. Fair and Foul: Beyond the Myths and Paradoxes of Sport. 5th ed. Landham, MD: Rowman & Littlefield]. Much of the research into the ideological production in college athletics centres media coverage of two men's commercialized sports (American football and basketball) as the producers of ideologies and one subject (fans) as the consumers of ideologies. Less is known about how ideologies are produced, circulated, and ultimately reproduced amongst college athletes. To address this gap, I use [Althusser, Louis. 1971. Lenin and Philosophy. New York, NY: Monthly Review] approach to ideology to analyse 47 interviews with Olympic (or non-commercialized) college athletes. Findings position college sport as an ISA with at least three mechanisms - time, behaviour, and language - that hail participants to racist and sexist ideologies rooted in 'biological' difference. Findings also explore how college athletes question how their own bodies are constructed by dominant ideologies.